Assessment of estrus detection and insemination efficiency of AI workers in buffaloes through plasma progesterone profile under field conditions* - SHARMA, H C; DHAMI, A J; SHARMA, S K; SARVAIYA, N P; KAVANI, F S (The Indian Journal of Animal Sciences, 2011)
A study was carried out during breeding season on 225 normal cyclic buffaloes selected from 3 villages of Anand district in Gujarat, to evaluate progesterone profile at the time of insemination in relation to fertility status, and to assess whether inseminations are done at right time under field conditions. Nearly 70% buffaloes were inseminated when they had circulatory P4 profile less than 0.5 ng/ml, while 18.22 and 12.45% were inseminated with P4 values of 0.6–1.0 and >1.0 ng/ml. Maximum (56%) buffaloes conceived, which had basal (< 0.1 ng/ml) P4 profile at the time of insemination, while none of 28 buffaloes inseminated with P4 levels > 1.0 ng/ml conceived. The first AIs conception rates were 25.40, 37.83 and 31.37% based on 63, 111 and 51 inseminations performed by the 3 inseminators. The corresponding percentages of incorrect inseminations (plasma P4 >0.5 ng/ml) performed by 3 inseminators were 33.33, 23.42 and 43.13. Overall, the first service CR was 32.88% and incorrect inseminations occurred in 30.67% buffaloes, which included 12.44% luteal phase (P4 >1.0 ng/ml) inseminations. The mean plasma progesterone concentration at fertile estrus was significantly lower than the infertile estrus for all the 3 village centres, with the overall mean of 0.26±0.02 vs 0.97±0.13 ng/ml. However, there was no significant variation in the P4 values at estrus/AI among 3 centres. Pregnancy occurred in animals having low or basal progesterone level at AI, while those failed to conceive with higher progesterone profile at AI suggested that they were not in true estrus, when inseminated. The village-wise results indirectly reflected the estrus detection and insemination efficiency of 3 inseminators. These findings clearly suggest the immediate need of imparting quality practical training and periodical assessment of performance of lay inseminators to improve their skill and knowledge of estrus detection and insemination. Otherwise, they would add significantly more man-made infertility to already existing problem under field conditions.